Pengaruh Konsentrasi Kepemilikan, dan Keterbukaan, Diversifikasi, Terhadap Risiko Bank - Prathama Nugraha; Risal Rinofah (JURNAL MANAJEMEN, 2014)
Bank is a financial institution that must able to guarantee the funds entrusted by the community. This guarantee related to the ability of banks to maintain their risk levels. As revealed by the theories and previous studies, a bank level of risk taking might determined by the concentration of the ownership, a party that determines the bank management. Additionally compliance in carrying out the principles of openness and the ability of banks to obtain other revenues outside the main business as intermediaries of funds from customers to the creditors also shown to determine the level of bank risk taking. By using multiple regression analysis techniques and observation of data during a period of 5 years, this study found that the level of a bank's risk taking is influenced by the disclosure of information and income diversification. The higher the index the information disclosure and diversification the lower the risk. Ownership concentration has shown the right coefficient direction corresponding to the risk but it is not statistically significant. Key Words: Risk Taking, Ownership Concentrations, Information Disclosure, Bank Income Diversification.